Recombinant scFv Antibodies against P30 Surface Protein of Toxoplasma Gondii - Mehdi Golchin; Mohadeseh Nakhaei-Moghadam; Saeid Reza Nourollahi-Fard (Journal of Kerman University of Medical Sciences, 2015)
Background & Aims: Toxoplasma gondii is an obligate, intracellular parasite, which is widely spread in the world. The parasite is able to infect all warm-blooded hosts including humans and farm animals. The infection in humans often occurs after the ingestion of raw or undercooked meat containing tissue cysts. Several methods have been applied to detect this parasite in contaminated foods. Recombinant antibodies are new generation of monoclonal antibodies, which are isolated via phage display technology from immune or non-immune phage libraries against target antigens. These antibodies are used for diagnosis of many different antigens and therapeutics proposes. The object of the present study was to isolate recombinant monoclonal antibodies against this important parasite. Methods: The purified Toxoplasma gondii surface antigen, P30, was coated to immunotubes and used as a target for selection of antibodies from the Tomlinson I and J phage display libraries of single-chain fragment variable (scFv) antibodies. Clones that were able to recognize antigen were isolated in three rounds of binding, elution and amplification. The specificity of scFv antibodies chosen from the resulting panel, were confirmed using enzyme-linked immunosorbent assay (ELISA), dot blotting and western blotting methods. Results: Recombinant antibodies capable of recognizing P30 antigen were isolated with high affinity; and their specificity was approved. Conclusion: Isolated soluble single chain antibodies are good candidates to apply as monoclonal recombinant antibodies in diagnostic kits for detection of Toxoplasma gondii in contaminated samples.